2017
DOI: 10.3201/eid2303.160101
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Fluctuations and Triggers of Ebola Virus Spillover

Abstract: Because the natural reservoir of Ebola virus remains unclear and disease outbreaks in humans have occurred only sporadically over a large region, forecasting when and where Ebola spillovers are most likely to occur constitutes a continuing and urgent public health challenge. We developed a statistical modeling approach that associates 37 human or great ape Ebola spillovers since 1982 with spatiotemporally dynamic covariates including vegetative cover, human population size, and absolute and relative rainfall o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…EMXT, the highest monthly daily maximum temperature, was a significant predictor for the number of Ebola spillover events in humans and animals. These results align to previous studies that have found a climatic dimension for Ebola spillover events (Tucker et al 2002; Pigott et al 2014; Schmidt et al 2017). In our study, however, we could additionally show that plant phenology variables [including the anomaly of Normalized Difference Vegetation Index (NDVI) between July and December, the proportion of population fruiting in Kibale National Park, Uganda, and the flowering anomalies in Lope, Gabon] informed neural network models with a superior fit to the data than when climate or climate in conjunction with phenology variables were used as inputs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…EMXT, the highest monthly daily maximum temperature, was a significant predictor for the number of Ebola spillover events in humans and animals. These results align to previous studies that have found a climatic dimension for Ebola spillover events (Tucker et al 2002; Pigott et al 2014; Schmidt et al 2017). In our study, however, we could additionally show that plant phenology variables [including the anomaly of Normalized Difference Vegetation Index (NDVI) between July and December, the proportion of population fruiting in Kibale National Park, Uganda, and the flowering anomalies in Lope, Gabon] informed neural network models with a superior fit to the data than when climate or climate in conjunction with phenology variables were used as inputs.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, however, we could additionally show that plant phenology variables [including the anomaly of Normalized Difference Vegetation Index (NDVI) between July and December, the proportion of population fruiting in Kibale National Park, Uganda, and the flowering anomalies in Lope, Gabon] informed neural network models with a superior fit to the data than when climate or climate in conjunction with phenology variables were used as inputs. Previous studies using Normalized Difference Vegetation Index or Enhanced Vegetation Index have not yet considered their predictive power for Ebola spillover events independently from climate variables (see Schmidt et al 2017). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By phenomenological, we mean approaches that relate the observed spillover events, z, as the dependent variable to some linear or nonlinear function of predictor variables, X, and coefficients b (e.g. [5,8,9]). Alternatively, one could combine information on host species density, prevalence, contact rate and infection rates to predict the number of spillovers,ẑ, [7] even when observed data on spillovers are rare or non-existent.…”
Section: Introductionmentioning
confidence: 99%